New taxonomic and distributional information on hermit crabs (Crustacea: Anomura: Paguroidea) from the Gulf of Mexico, Caribbean Sea, and Atlantic coast of South America - Lemaitre, Rafael; Tavares, Marcos (Zootaxa, 2015)
A collection of Paguroidea recently obtained during deep-water expeditions along the coast of Brazil, forms the basis of this report. Of the 14 species reported from Brazil, 11 represent range extensions to the south, and one, Michelopagurus atlanticus (Bouvier, 1922), is a first record for the western Atlantic. The specimens were compared with types and western Atlantic materials deposited in various major museums. A diagnosis and illustrations are presented for each of seven species found to be poorly or insufficiently known. New material and information is reported for two additional species that occur in Brazil but not found in the recent deep-water collections: Clibanarius symmetricus (Randall, 1840) and Mixtopagurus paradoxus A. Milne-Edwards, 1880. Remarkable and unique color photographs of live or fresh specimens of Allodardanus bredini Haig & Provenzano, 1965, Bathynarius anomalus (A. Milne-Edwards & Bouvier, 1893), Pylopagurus discoidalis (A. Milne-Edwards, 1880), Paguristes spinipes A. Milne-Edwards, 1880, Parapagurus pilosimanus Smith, 1876, and P. alaminos Lemaitre, 1986, are presented. A review of published records and museum collections of the terrestrial Coenobita clypeatus (Fabricius, 1787), has shown that the southern range limit of this species does not extend beyond the southern Caribbean and Trinidad and Tobago, and thus does not occur on the Brazilian coast as previously believed. A distribution map of C. clypeatus is provided based on specimens in the collections of the National Museum of Natural History, Smithsonian Institution. New distribution records in the Gulf of Mexico and southern Caribbean, and morphological information, are included for Pagurus rotundimanus Wass, 1963, a species originally described from the Florida Keys but rarely reported since. Relevant remarks on the taxonomy, morphology, and distribution of all these species are included. The revised list of Paguroidea known from Brazil is updated, and now includes a total of 62 species in the families Pylochelidae (1), Diogenidae (27), Paguridae (28), and Parapaguridae (6). A synopsis of primary taxonomic works on western Atlantic Paguroidea is also presented.